An FEM investigation into the behaviour of metal matrix composites: tool–particle interaction during orthogonal cutting - Pramanik, Alokesh; Zhang, Liangchi; Arsecularatne, Joseph (ELSEVIER, 2007)
An analytical or experimental method is often unable to explore the behavior of a metal matrix composite (MMC) during machining due to the complex deformation and interactions among particles, tool and matrix. This paper investigates the matrix deformation and tool–particle interactions during machining using the finite element method. Based on the geometrical orientations, the interaction between tool and particle reinforcements was categorized into three scenarios: particles along, above and below the cutting path. The development of stress and strain fields in the MMC was analyzed and physical phenomena such as tool wear, particle debonding, displacements and inhomogeneous deformation of matrix material were explored. It was found that tool–particle interaction and stress/strain distributions in the particles/matrix are responsible for particle debonding, surface damage and tool wear during machining of MMC.